LmjMAPK10 offers protection against Leishmania donovani infection. (27th January 2020) - Kumar, Sunil; Zutshi, Shubhranshu; Patidar, Ashok; Bodhale, Neelam; Roy, Somenath; Sarkar, Arup; Saha, Bhaskar
Abstract: Aims: This study aimed at evaluating the DNA vaccination efficacy of Leishmania major ‐derived MAPK10 against Leishmania donovani infection. Methods and Results: MAPK10 is one of the 15 mitogen‐activated protein kinases (MAPKs) of Leishmania major . Herein, we expressed the gene through a mammalian vector and tested whether priming with this gene would offer protection against L donovani infection. We report that LmjMAPK10 DNA vaccination using a mammalian expression vector significantly reduces the parasite burden. The protection is accompanied by host‐protective T‐cell functions, TH 1‐type cytokines and elevated leishmanial antigen‐specific IgG2a isotype response. T‐cell response to the L donovani /challenge infection is associated with increase in IL‐12 and IFN‐γ, but reduced IL‐10 and IL‐4 production. Conclusions: LmjMAPK10 is cross‐protective against L donovani infection.